2018
DOI: 10.3390/v10040160
|View full text |Cite
|
Sign up to set email alerts
|

Allelic RNA Motifs in Regulating Systemic Trafficking of Potato Spindle Tuber Viroid

Abstract: Intercellular RNA trafficking has been shown as a widely-existing phenomenon that has significant functions in many aspects of biology. Viroids, circular noncoding RNAs that cause plant diseases, have been a model to dissect the role of RNA structural motifs in regulating intercellular RNA trafficking in plants. Recent studies on potato spindle tuber viroid (PSTVd) showed that the RNA motif loop 19 is important for PSTVd to spread from palisade to spongy mesophyll in infected leaves. Here, we performed saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…To our knowledge, this is the first report of an RNA 3D structural motif with this specific function. Previous studies have shown that a PSTVd 3D motif (loop 7) mediates vascular entry [30], and that trafficking from palisade mesophyll to spongy mesophyll in N. benthamiana involves 3D motifs in loop 6 and loop 19 [3133]. Sequences adjacent to loop 8 and within loop 24 have been shown to constitute a bipartite motif responsible for directional trafficking from bundle sheath to mesophyll cells in young tobacco ( N .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first report of an RNA 3D structural motif with this specific function. Previous studies have shown that a PSTVd 3D motif (loop 7) mediates vascular entry [30], and that trafficking from palisade mesophyll to spongy mesophyll in N. benthamiana involves 3D motifs in loop 6 and loop 19 [3133]. Sequences adjacent to loop 8 and within loop 24 have been shown to constitute a bipartite motif responsible for directional trafficking from bundle sheath to mesophyll cells in young tobacco ( N .…”
Section: Discussionmentioning
confidence: 99%
“…We are using Potato spindle tuber viroid (PSTVd) to investigate the roles of unique structural motifs in RNA trafficking. To date, several motifs that mediate passage across distinct cellular boundaries have been identified [2933]. However, an element necessary for PSTVd trafficking between upper epidermal cells and immediately underlying palisade mesophyll cells, which represents an early step in systemic infection initiated by mechanical leaf abrasion (rub inoculation), has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Mutational studies followed by bioassays in planta and in protoplasts identified other loops and bulges in the most stable secondary structure of PSTVd with potential functional roles in its replication and/or trafficking (42) (Figure 3). Some of these loops were shown to be highly structured 3D motifs, the disruption of which impaired viroid movement and/or replication (43)(44)(45)(46). Interestingly, the progeny of a variant mutated in one of the loops involved in PSTVd trafficking (loop 19, Figure 3) recovered movement competence when an alternative 3D motif replaced the mutation (45), thus revealing that functionally relevant tertiary structural elements may emerge de novo and likely act as critical constrains in viroid evolution (47).…”
Section: Secondary Structures 3d Motifs and Metastable Conformations ...mentioning
confidence: 99%
“…However, most loops in RNA molecules have three-dimensional (3D) structures stabilized by non-canonical base pairs and other base interactions [ 48 , 49 ]. PSTVd RNA is no exception, and specific functions have been ascribed to many of the structured loops [ 31 34 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, most loops in RNA molecules have three-dimensional (3D) structures stabilized by non-canonical base pairs and other base interactions [48,49]. PSTVd RNA is no exception, and specific functions have been ascribed to many of the structured loops [31][32][33][34]50,51]. When mapped to the (+)-strand secondary structure of the PSTVd genome, unshared de novo mutations (polymerase errors) were observed throughout and affected both stems (secondary structure) and loops (3D structure) ( Fig 5B).…”
Section: Transcription Errors Cluster In Distinct Regionsmentioning
confidence: 99%